(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the tasks of physical education for students, the forms and tools of activities, as well as the content and structure of lessons, highlighting the importance of physical education in the educational process. It examines the main objectives of physical education, such as promoting a healthy lifestyle, increasing physical activity, and improving students’ psychological well-being. The article also analyzes how physical education impacts students’ overall development, fosters a healthy lifestyle, and enhances team spirit. Through this, it aims to help develop the knowledge and skills necessary for organizing students’ physical education more effectively.